The 1919 Georgia-Azerbaijan Treaty of Collective Security and Mutual Assistance and its Consequences: Sokhumi State University - Gaprindashvili, Giorgi (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2025)
In May 1918, four sovereign states emerged in the Caucasus. Georgia, Armenia, Azerbaijan and the Mountainous Republic. They faced challenging operational conditions, including an economy devastated in the aftermath of World War I, undefined state borders, and imminent foreign threats. Addressing these seemingly insurmountable challenges appeared implausible. However, our research reveals a different narrative: Georgia endeavored to perpetuate its centuries-old mission, embarking on a successful journey of integration with its Caucasian counterparts. The meeting of 1919 was distinguished by the fact that all four states of the Caucasus participated in it. The impetus for championing this idea at that specific moment likely drew inspiration from the experience of the ,,Triple Alliance“ and ,,Entente,“ a known entity to Georgians. Notably, during World War I, members of the ,,Committee of the Liberation of Georgia“ were primarily active in Europe. They were well aware of the importance of military-political alliances. By 1919, both Georgians and Azerbaijanis felt the danger coming from the north and the need for unity. The pinnacle of this integration was the subsequent deployment of the international Caucasian coalition to Dagestan under the leadership of Georgian Colonel Leo Kereselidze. It should be noted that this agreement preceded the development of the League of Nations charter, one of the goals of which was the peaceful resolution of conflicts and wars, which provided for the use of negotiations and arbitration to resolve the issue. Based on this scientific innovations, these processes was clearly a great achievement for the three-year period of independence filled with challenges.